Propargyl 1,2-orthoesters as glycosyl donors: stereoselective synthesis of 1,2-trans glycosides and disaccharides - Sureshkumar, Gopalsamy; Hotha, Srinivas (Tetrahedron Letters, 2007)
Propargyl 1,2-orthoesters are identified as glycosyl donors. Various glycosides and disaccharides were synthesized in a stereoselective manner using AuBr3 as the promoter. AuBr3 may activate the alkyne resulting in the formation of a 1,2-dioxolenium ion and also behaves as a Lewis acid to facilitate the attack of the glycosyl acceptor. The versatility of the protocol was demonstrated using a panel of aglycones comprising aliphatic, alicyclic, steroidal and sugar alcohols. (C) 2007 Elsevier Ltd. All rights reserved.

Gold mediated glycosylations: selective activation of propargyl 1,2-orthoesters in the presence of aglycones containing a propargyl moiety - Sureshkumar, Gopalsamy; Hotha, Srinivas (Chemical Communications, 2008)
Selective activation of propargyl 1,2-orthoesters in the presence of propargyl glycosides and propargyl ethers was studied; a catalytic amount of AuBr(3) activated the propargyloxy, group of the 1,2-orthoester thereby giving access to disaccharides with the propargyl group at the reducing end; furthermore, propargyl ethers were unaffected under the reaction conditions.

Enhanced DNA binding of 9-omega-amino alkyl ether analogs from the plant alkaloid berberine - Islam, Md Maidul; Basu, Anirban; Hossain, Maidul; Sureshkumar, Gopalsamy; Hotha, Srinivas; Kumar, Gopinatha Suresh (DNA and Cell Biology, 2011)
To understand the structure-activity relationship of isoquinoline alkaloids, absorption, fluorescence, circular dichroism, and thermodynamics were employed to study the interaction of five C-9-omega-amino alkyl ether analogs from the plant alkaloid berberine with double-stranded calf thymus DNA. The C-9 derivatization resulted in dramatic enhancements in the fluorescence emission of these compounds. The most remarkable changes in the spectral and binding properties were in the BC4 and BC5 derivatives. Interactions of these analogs, which have an additional recognition motif with DNA, were evaluated through different spectroscopic and calorimetric titration experiments. The analogs remarkably enhanced the DNA binding affinity and the same was directly dependent on the alkyl chain length. The analog with six alkyl chains enhanced the DNA binding affinity by about 33 times compared with berberine. The binding became more entropically driven with increasing chain length. These results may be of potential use in the design of berberine derivatives and understanding of the structure-activity relationship for improved therapeutic applications.

Facile synthesis of unusual glycosyl carbamates and amino acid glycosides from propargyl 1,2-orthoesters as glycosyl donors - Shaikh, Ashif Y.; Sureshkumar, Gopalsamy; Pati, Debasish; Sen Gupta, Sayam; Hotha, Srinivas (Organic & Biomolecular Chemistry, 2011)
Propargyl 1,2-O-orthoesters are exploited for the synthesis of 1,2-trans O-glycosides of protected amino acids. N-Fmoc- and N-Cbz protected serine/threonine - benzyl/methyl esters reacted well with glucosyl-, galactosyl-, mannosyl- and lactosyl- derived propargyl 1,2-orthoesters affording respective 1,2-trans glycosides in good yields under AuBr(3)/4 angstrom MS Powder/CH(2)Cl(2)/rt. t-Boc serine derivative gave serine 1,2-orthoester and glycosyl carbamate. Optimized conditions enabled preparation of new glycosyl carbamates from N-Boc protected amines in a single step using gold catalysts and propargyl 1,2-orthoesters in excellent yields.